2021
DOI: 10.3390/ijms22116108
|View full text |Cite
|
Sign up to set email alerts
|

Docking-Based 3D-QSAR Studies for 1,3,4-oxadiazol-2-one Derivatives as FAAH Inhibitors

Abstract: This work aimed to construct 3D-QSAR CoMFA and CoMSIA models for a series of 31 FAAH inhibitors, containing the 1,3,4-oxadiazol-2-one moiety. The obtained models were characterized by good statistical parameters: CoMFA Q2 = 0.61, R2 = 0.98; CoMSIA Q2 = 0.64, R2 = 0.93. The CoMFA model field contributions were 54.1% and 45.9% for steric and electrostatic fields, respectively. In the CoMSIA model, electrostatic, steric, hydrogen bond donor, and hydrogen acceptor properties were equal to 34.6%, 23.9%, 23.4%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A 3D-QSAR CoMSIA study was previously performed on 90 pyrimidinyl-piperazinecarboxamide derivatives that irreversibly inhibit FAAH and concluded that electrostatic and hydrogen-bond acceptor properties are the most important for the activity of these types of compounds [46]. Similar 3D-QSAR CoMFA and CoMSIA models were constructed for a series of 1,3,4-oxadiazol-2-one derivatives [50]. The importance of the 1,3,4-oxadiazol-2-one scaffold was revealed also in our study by the high P-PR value of fragment PR21.…”
Section: Discussionmentioning
confidence: 99%
“…A 3D-QSAR CoMSIA study was previously performed on 90 pyrimidinyl-piperazinecarboxamide derivatives that irreversibly inhibit FAAH and concluded that electrostatic and hydrogen-bond acceptor properties are the most important for the activity of these types of compounds [46]. Similar 3D-QSAR CoMFA and CoMSIA models were constructed for a series of 1,3,4-oxadiazol-2-one derivatives [50]. The importance of the 1,3,4-oxadiazol-2-one scaffold was revealed also in our study by the high P-PR value of fragment PR21.…”
Section: Discussionmentioning
confidence: 99%
“…One of the significant advantages of this approach is its immediate application in the examination of any structure-dependent biological characteristics. 22 The CoMFA theory states that differences in a target property between chemicals are frequently associated with changes in the noncovalent fields that surround those structures. These fields, which are the electrostatic (Coulombic) and steric (Lennard-Jones) fields, are computed at regular intervals within a predetermined area.…”
Section: Generation Of 3d-qsar By Comfamentioning
confidence: 99%
“…The in-depth analysis process is described in the Supplementary Material under the Methodology Section. The progressive scrambling study was conducted as described in this study [49].…”
Section: Dataset Building Molecular Alignment and Comfa-comsia (3d-qsar) Studymentioning
confidence: 99%